New insights into the in vitro biological effects, in silico docking and chemical profile of clary sage - Salvia sclarea L. - DOĞAN, AHMET; EMRE, GİZEM; ŞENKARDEŞ, İSMAİL (ELSEVIER SCI LTD, 2018)
Salvia sclarea L. is traditionally used to manage common human ailments and is consumed as a food product. This study aimed to establish the phytochemical profile and antioxidant potential of ethyl acetate, methanol, and water extracts of Salvia sclarea. The inhibitory action of the extracts against alpha-amylase, alpha-glucosidase, acetyicholinesterase, butyrylcholinesterase, and tyrosinase was also investigated. Methanol extract showed the highest phenolic and fiavonoid contents (81.78 mg GAE/g extract and 40.59 mg RE/g extract, respectively). Reversed phase high performance liquid chromatography with diode array detector analysis revealed that S. sclarea was rich in rosmarinic acid. The water extract exhibited the lowest inhibitory activity against alpha-amylase but the upmost activity against alpha-glucosidase (0.19 and 18.24 mmol ACAE/g extract, respectively). Experimental data showed that only the water extract (8.86 mg KAE/g extract) significantly inhibited tyrosinase. Docking studies showed that quercetin binds to tyrosinase by two hydrogen and a pi-pi bonds. Salvia sclarea showed interesting biological activity against key enzymes involved in the pathogenesis of common ailments. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Salvia; Clary sage; Natural enzyme inhibitors; Molecular docking; TOTAL FLAVONOID CONTENT; ALPHA-GLUCOSIDASE; ROSMARINIC ACID; ALZHEIMERS-DISEASE; ANTIOXIDANT ACTIVITY; ANTIMICROBIAL ACTIVITY; PHYTOCHEMICAL PROFILE; INHIBITORY-ACTIVITIES; ESSENTIAL OIL; TYROSINASE